The lived experience of healthcare professionals working frontline during the 2003 SARS epidemic, 2009 H1N1 pandemic, 2012 MERS outbreak, and 2014 EVD epidemic: A qualitative systematic review - Erin R. Chahley; Riley M. Reel; Steven Taylor (Elsevier, 2021)
Objective: To synthesize qualitative literature exploring the lived experience of healthcare workers (HCWs) who cared for patients during the following infectious disease outbreaks (IDOs): the 2003 SARS epidemic, 2009 H1N1 pandemic, 2012 MERS outbreak, and 2014 EVD epidemic. We aim to reveal the collective experience of HCWs during these four IDOs and to create a reference for comparison of current and future IDOs. Methods: Three electronic databases were searched, yielding 823 results after duplicates were removed. Forty qualitative and mixed-methods studies met the criteria for full file review. Fourteen studies met the inclusion and exclusion criteria. The data from the Results or Findings sections were manually coded and themes were conceptualized using thematic analysis. Results: Of the 14 studies, 28.6% focused on SARS, 21.4% on H1N1, 21.4% on MERS, and 28.6% on EVD. Studies occurred in six different countries and included physicians, nurses, paramedics, and emergency medical technicians as participants. Five themes were conceptualized: Uncertainty, Adapting to Change, Commitment, Sacrifice, and Resilience. Conclusion: This review identified the collective experience of HCWs caring for patients during four 21st century IDOs. This qualitative systematic review offers a reference to compare similarities and differences of other IDOs, including the COVID-19 pandemic.